Identification of lncRNAs Associated With Neuroblastoma in Cross-Sectional Databases: Potential Biomarkers - Prajapati, Bharat; Fatma, Mena; Fatima, Mahar; Khan, Md Tipu; Sinha, Subrata; Seth, Prahlad K. (Frontiers in Molecular Neuroscience, 2019)
Long non-coding RNAs (lncRNAs) have emerged as an important regulatory control in biological systems. Though the field of lncRNA has been progressing rapidly a complete understanding of the role of lncRNAs in neuroblastoma pathogenesis is still lacking. To identify the abrogated lncRNAs in primary neuroblastoma, and in metastasized as well as relapsed form of neuroblastoma, we analyzed online available RNA-seq dataset on neuroblastoma to identify the implicated lncRNAs that could be potentially contributing to the biology of neuroblastoma. The identified lncRNAs were further scrutinized on publicly available epigenetic dataset of neuroblastoma and cancer databases. After this cross-sectional study, we were able to identify three significant lncRNAs CASC15, PPP1R26-AS1 and USP3-AS1 which could serve as potential biomarkers in the clinical studies of neuroblastoma pathogenesis.